Zoology - Miller, Stephen A.; Tupper, Todd A. (New York: McGraw Hill, 2024)
"As the senior author of Zoology, I (Stephen Miller) am very pleased to present the Twelfth edition of this textbook. I have been associated with this book from its inception. The initial planning, writing, and revision of Zoology through preparing this latest edition involved tasks that have spanned more than 30 years of my life. I am honored to have played a small part in the training of zoologists and other biologists, most of whom I will never know personally. Similarly, it has been an honor to feel a connection to the professors who use Zoology in their courses and who deserve the credit for mentoring future scientists. The processes of writing and revision have involved many joys, and some headaches, for me personally. I hope these efforts have helped inspire bright young minds to strive to make our planet a better place than Earth would have otherwise been"--
Includes index.
Keywords: Zoology